Squamous Cell Carcinoma: Prevention And Early Diagnosis In Dentistry - Muñante Cárdenas, José Luis (2013)
Squamous cell carcinoma (SCC) is the most prevalent malignancy in the oral cavity. Because most of the SCC cases are diagnosed late, treatment has been linked to radical and disfiguring surgery, as well as high rates of recurrence and unfavorable forecasts. Currently, technological advances allow more conservative surgical treatments. In addition, new models of chemotherapy and radiotherapy significantly affect treatment and outcome of patients. However, some researchers have reported only a small improvement in the survival rate in advanced SCC, the same that continues presenting an extremely poor prognosis. SCC initial cases have a better prognosis when compared to advanced cases. Therefore, the prevention, early diagnosis and prompt treatment setting are essential to prevent premature deaths, aesthetic disfigurement and functional sequels caused by this disease.